2004
DOI: 10.1007/s00221-003-1647-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of motor imagery in learning a totally novel movement

Abstract: The aim of the present study is to gain more insight into the mechanisms underlying mental practice. The question of whether a totally novel movement may be learned by mental practice was investigated. Healthy young adults had to learn the abduction of the big toe (dominant right foot) without moving the other toes or the foot. The subjects were divided into two groups: subjects who were absolutely unable to abduct their big toe ("absolute zero" group) and subjects who were able to abduct their toe to some ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
1
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 38 publications
10
98
1
18
Order By: Relevance
“…Conversely, provided that the pinch value obtained does not represent convergence on 50% MVC, the 50% MVC error is increased in the second than that in the first trial of the pinch task. Given these observations, our results suggest that motor imagery does not improve the ability to achieve accurate motion after motor learning for 10 s. Mulder et al [22] reported that motor imagery improved the ability to achieve actual motion only in people with learning that corresponded to the motor imagery task. Accordingly ,thesubjectsmightnotbeabletolearn the 50% MVC in only 10 s. Thus, it is necessary for the learning of subjects to correspond fully t ot h em o t o rt a s k .W ec o n c l u d et h a ta d e q u a t el e a r n i n gt i m es h o u l db ep r o v i d e di nf u t u r e studies.…”
Section: The Effect Of Motor Imagery On the Accuracy Of Motionmentioning
confidence: 53%
“…Conversely, provided that the pinch value obtained does not represent convergence on 50% MVC, the 50% MVC error is increased in the second than that in the first trial of the pinch task. Given these observations, our results suggest that motor imagery does not improve the ability to achieve accurate motion after motor learning for 10 s. Mulder et al [22] reported that motor imagery improved the ability to achieve actual motion only in people with learning that corresponded to the motor imagery task. Accordingly ,thesubjectsmightnotbeabletolearn the 50% MVC in only 10 s. Thus, it is necessary for the learning of subjects to correspond fully t ot h em o t o rt a s k .W ec o n c l u d et h a ta d e q u a t el e a r n i n gt i m es h o u l db ep r o v i d e di nf u t u r e studies.…”
Section: The Effect Of Motor Imagery On the Accuracy Of Motionmentioning
confidence: 53%
“…The statistical data show a surprising progress of the mental group compared to the two other groups (observational group and the analytical group).These findings go in the same direction as those observed in the work of Crosbie & al., (2004). Other authors note the importance of imagery in the acquisition of new techniques such as Mulder & al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Yue (1992), Yaguez (1998), Vielledent (2003), and Mulder (2004) proved that mental practice leads to improvement in motor performance and can have an effect on brain activities during and after mental practice period. In this way, the motor programme is established and the level of muscle activity is mentally regulated (16)(17)(18)(19). Bohan et al (1999) investigated the performance effects of imagery practice at three stages of learning a novel motor task.…”
Section: Introductionmentioning
confidence: 99%